NURTURING LITERACY DEVELOPMENT FOR EARLY EDUCATION IN PAPUA - Yohana Yembise (Journal of Education Papua Baru, 2023)
Papua is home to numerous local cultures and languages. Early literacy programs help preserve and promote these cultural heritages, ensuring they are passed down to future generations.  Early literacy promotes social inclusion by enabling children to participate fully in their communities, family, schools, and society at large. It fosters a sense of belonging and equal participation for all, irrespective of linguistic or cultural backgrounds. The paper explores through related references on the multidimensional background of literacy initiatives and challenges in the Papua region. It offers a concise preview of the subject matter, emphasizing the significance of literacy as a critical factor in social and educational progress. It invites readers to explore into the complexities and dynamics of literacy development efforts within Papua, ultimately contributing to a deeper understanding of the region's educational aspirations and potential pathways for improvement.  A significant discovery concerning regional statistical data indicates a clear correlation between areas or districts with a high illiteracy rate and those experiencing elevated levels of poverty. Suggestion for urgent further investigation is required to address future literacy improvement in these specific regions within Papua. Keywords: Literacy, Early Education Papua memiliki beragam kekayaan budaya dan bahasa lokal.  Program literasi awal mempunyai peran yang krusial dalam melestarikan dan mempromosikan warisan budaya ini, serta memastikan agar pengetahuan tersebut dapat diwariskan kepada generasi yang akan datang. Literasi awal mendukung inklusi sosial dengan memberikan kesempatan kepada anak-anak untuk terlibat sepenuhnya dalam komunitas, keluarga, sekolah, dan masyarakat secara keseluruhan. Hal ini tentu saja berkontribusi dalam menciptakan persatuan dan partisipasi yang setara bagi semua individu, tanpa memandang latar belakang linguistik atau budaya yang mereka miliki. Paper ini menggali latar belakang yang kompleks dari upaya pengembangan literasi dan tantangan yang dihadapi di wilayah Papua berdasarkan sumber-sumber yang relevan. Disamping itu juga memberikan ringkasan singkat mengenai isu pokok yang menekankan betapa pentingnya literasi bagi kemajuan sosial dan pendidikan. Hal ini mendorong pembaca untuk lebih mendalami kompleksitas dan dinamika upaya pengembangan literasi di Papua, yang pada akhirnya akan meningkatkan pemahaman kita tentang aspirasi pendidikan di wilayah ini dan kemungkinan langkah-langkah perbaikan yang dapat diambil. Temuan signifikan yang berkaitan dengan data statistik regional menunjukkan adanya korelasi yang jelas antara daerah-daerah yang tingkat buta huruf tinggi dengan daerah-daerah yang tingkat kemiskinannya tinggi. Oleh karena itu, disarankan adanya urgensi penelitian lebih lanjut kedepan tentang pengembangan literasi yang difokuskan di daerah-daerah  tersebut di Papua. Kata Kunci : Literasi, Pendidikan Usia Dini